ETIKA BISNIS PEDAGANG MUSLIM DILIHAT DARI PERSEPEKTIF ISLAM DAN DAMPAKNYA TERHADAP KESEJAHTERAAN PEDAGANG DI PASAR TRADISIONAL KOTA MATARAM - Moh. Huzaini; Akhmad Jupri; Ihsan Ro’is; Musta’in Musta’in (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2019)
Abstract: This study aims to determine the types of goods traded by Muslim traders, to analyze the Business Ethics of Muslim Traders viewed from an Islamic perspective and to analyze the welfare conditions of Muslim traders from an Islamic perspective in the Mataram Traditional Market. This study uses qualitative methods, because it examines reality, phenomena or symptoms that are holistic / intact, complex, dynamic and full of meaning. Data collection techniques carried out by observation, interviews, sound recordings and photographs. Informants were determined while in the field using snowball sampling techniques. Analysis of the data used is qualitative analysis. Research conclusions: 1. There are six groups of goods traded, namely: agricultural products, home industry, fishery products, food, various types of snacks and various types of culinary; 2. Most traders have adopted Islamic business ethics, for example not using fake oaths, being loose and generous, building good relationships and setting prices transparently. Some of them have not fully implemented Islamic business ethics, for example, not being honest in selling, not being loose and generous and not building a good relationship with customers; 3. Most traders have gotten a good life (hayaatan tayyibah) and have been qana’ah, even though they live in simplicity. They are also included in a prosperous family, because they have been able to meet the needs of dharuriyyat and hajiyat. Some others do not include a prosperous family, because it has not been able to meet the needs of dharuriyyat (hifzun-nafs).